A Retrospective Analysis of the Acquisition of Target’s Pharmacy Business by CVS Health: Labor Market Perspective - Farag, Enas; Abdelfattah, Alaa; Compton, Chris; Stansbury, Anna; Steinbaum, Marshall (The Review of Economics and Statistics, 2026)
We analyze the labor market impact of CVS Health’s acquisition of Target’s pharmacy business in December 2015 using Lightcast job postings data. Using differencein- differences and triple-difference designs, we find meaningful negative effects of the merger on posted pay. In our preferred specification, we estimate that the acquisition reduced posted pay in affected labor markets by 2.9%. We test for heterogeneous merger effects by occupational characteristics, finding that the merger caused pay to fall by more in lower-paid occupations than in higher-paid occupations.